History of my father mogorotoɨ ‘blue macaw’: words of the ritual of the fruits, which come to us as food in abundance, as told by the okaina ethnic group (2011)
Bilingual Witoto-Spanish text about the origin and stages of the yuakɨ ritual dance (ritual of the fruits), which is celebrated by the Witoto and other neighboring groups of the Caqueta-Putumayo interriverine region in the Colombo-Peruvian Amazon. This text was written by an indigenous woman in the buue dialect of the Witoto language from the memories of the speeches of her father in the “yard of tobacco and coca” when she was a child.